Effect of Periodized Interval Training in Combination with Explosive Strength and Speed in Game-Like Situation on Agility and High Intensity Aerobic Capacity of Youth Soccer Players - Kabdwal, Mahesh Chandra; Pal, Shubham; Poonia, Rina (Physical Education Theory and Methodology, 2023)
Study purpose. High-intensity aerobic capacity (HIAC) is essential for soccer players because they have to perform sprints of short duration in the shortest possible time. At the same time, they need to quickly change direction with and without the ball, which requires agility. The purpose of the study was to investigate the effect of a periodized (8-week) training plan that combines interval training (IT), explosive strength (ES), speed, and game-like situations on agility and HIAC in youth soccer players. Materials and methods. This research is an experimental study in which the population was male youth soccer players (N = 23) (aged 16.7±2.1). The Arrowhead Agility Test and the HIAC Yo-Yo Intermittent Recovery Test Level 1 (YYIR1) have taken the pre- and post-data of agility. By using the formula for YYIR1 test: VO₂max (mL kg-1 min-1) = IR1 distance (m) × 0.0084 + 36.4, we get an estimation of the volume of maximum oxygen consumption (VO₂max). The data analysis used a t-test at 0.05% as the significance level. Results. Based on the results, the mean of the pre-tests in agility, YO-YO IR1, and VO₂max showed 17.911, 14.8100, and 55.25510. After training for eight weeks, there was an improvement: the mean showed 16.667, 15.9750, and 60.06960. As per the results of the data on the hypothesis in the study, it was found that there was a significant effect of periodized IT in combination with ES and speed on agility performance and HIAC of the youth soccer players. Conclusions. There was a significant effect of periodized IT in combination with ES and speed on improving youth soccer players’ agility performance and HIAC.